Amphetamine Containing Dietary Supplements and Acute Myocardial Infarction - Julio Perez-Downes; Abdulwahab Hritani; Candice Baldeo; Patrick Antoun (Case Reports in Cardiology)
Weight loss is one of the most researched and marketed topics in American society. Dietary regimens, medications that claim to boost the metabolism, and the constant pressure to fit into society all play a role in our patient’s choices regarding new dietary products. One of the products that are well known to suppress appetite and cause weight loss is amphetamines. While these medications suppress appetite, most people are not aware of the detrimental side effects of amphetamines, including hypertension, tachycardia, arrhythmias, and in certain instances acute myocardial infarction. Here we present the uncommon entity of an acute myocardial infarction due to chronic use of an amphetamine containing dietary supplement in conjunction with an exercise regimen. Our case brings to light further awareness regarding use of amphetamines. Clinicians should have a high index of suspicion of use of these substances when young patients with no risk factors for coronary artery disease present with acute arrhythmias, heart failure, and myocardial infarctions.